1985
DOI: 10.1111/j.2044-8260.1985.tb01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric coordination and focused attention in chronic and acute schizophrenia

Abstract: Groups of chronic and acute schizophrenics, together with controls, were given a story comprehension task where material was presented either binaurally or monaurally. A significant right ear advantage was found in the scores of the acute patients but not in those of chronics or controls. Similarly, acutes, in contrast to all other subjects, demonstrated a binaural performance decrement relative to their preferred ear in the monaural condition. A second experiment showed that acute schizophrenics, in contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…We noted, as have some (e.g. Green, 1985Green, , 1987 but not all other investigators (Galin eta!, 1990),a high rate of schizophrenic subjects with binaural deficits.…”
Section: Discussionsupporting
confidence: 61%
“…We noted, as have some (e.g. Green, 1985Green, , 1987 but not all other investigators (Galin eta!, 1990),a high rate of schizophrenic subjects with binaural deficits.…”
Section: Discussionsupporting
confidence: 61%
“…Measures included dichotic listening and shadowing, stereognosis, somatosensory evoked potentials to median nerve stimulation, flash evoked potentials, interocular transfer of movement aftereffects, and divided visual field color naming. A dominance of left-hemispheric influences, shown by difficulty in transmitting information from right to left, has been found in patients described as acute (Green et al 1983;Green 1985), paranoid (Bull 1972;Hammond 1979b, 1980), autonomically responsive (Gruzelier and Hammond 1979a, 1979b, 1980, actively psychotic (Buchsbaum et al 1979;Hammond 1979a, 1979b;Gulmann et al 1982), schizoaffective (Weller and Kugler 1979;Craft et al 1987), and having first-rank symptoms (David 1987). Such a profile is consistent with the aroused, active syndrome and it follows from their characteristic L > R imbalance that rightward transmission would be dominant over leftward transmission.…”
Section: Syndrome-related Asymmetries In Interhemispheric Connectivitymentioning
confidence: 99%
“…The performance of acute schizophrenics in all these studies was marked by a large asymmetry between the preferred and non-preferred ear in the monaural presentation conditions. In the P. Green & Kotenko (1980) and E. Green (1985) studies, all except a tiny minority of the patients showed superior performances with the right ear. These results are consistent with the interpretation that, due to impaired transfer across the corpus callosum, lateral asymmetries in performance resulting from functional specialization of the brain, masked in normal subjects because of very rapid callosal transmission, become apparent in schizophrenics.…”
mentioning
confidence: 87%
“…comprehension scores when material was presented binaurally rather than to one ear only. P. Green et al (1983) suggested that the binaural deficit was the result of impaired callosal transfer, while E. Green (1985) considered that it was caused by the inability of acute schizophrenics to attend successfully to one ear in the presence of stimulation to the other.…”
mentioning
confidence: 99%